PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL COOPERATIVE LEARNING TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR FISIKA RANAH KOGNITIF DAN SIKAP KERJA SAMA PESERTA DIDIK SMA - Solikhah, Nanda Annisa; Sukardiyono, Sukardiyono (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
This research aims to: (1) produce physics learning tools using the think talk write type cooperative learning model which are suitable for use to improve learning outcomes in the cognitive domain and cooperative attitudes of students and (2) determine the effectiveness of learning tools using the think talk write type cooperative learning model in improve cognitive learning outcomes and cooperative attitudes of students. This research is development research (RD) with a 4D model consisting of stages (1) define, (2) design, (3) develop, and (4) disseminate. The products developed are RPPs, LKPD, test question instruments, and cooperative attitude assessment questionnaires. The subjects in this research were students of SMA Negeri 1 Gamping class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. The results of the research show that: (1) the learning tools developed are suitable for use in physics learning with a very good category, (2) the learning tools developed are effectively used to improve learning outcomes in the cognitive domain of physics and the cooperative attitude of class XI high school students with effect scores. The size of the learning outcomes in the cognitive domain is 2.02, which is included in the very large category, and the effect size value for cooperative attitudes is 0.80, which is included in the medium category.